Pengembangan IoT Cloud Platform berbasis pada Layanan Serverless Computing - Refri Rifwan Daharmi; Adhitya Bhawiyuga; Achmad Basuki (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
IoT and Cloud integration is undoubtedly the best way to solve most IoT problems. IoT Cloud Platform development is carried out by creating programs in a complex application which is then loaded into a virtual environment on the cloud or known as Infrastructure-as-a-Service (IaaS). The use of IaaS has common problems related to operations such as resource provisioning, monitoring, maintenance, scalability, and fault tolerance. Therefore, it is necessary to develop an IoT Cloud Platform using a cloud mechanism as Function-as-a-Service (FaaS), which is a subset of serverless computing. Its application is carried out by building an IoT cloud platform architectural design including system component design, system communication design, and Auth Services architectural design. Next, implementation is carried out from the results of the architectural design that has been made and testing is carried out starting from testing the API service and testing performance. The tests carried out resulted in all system features being valid and the results of system performance testing being able to handle 28.85 requests per second for 50 requests simultaneously and increased for 100 and 150 requests with a result of 56.37 per second for 100 requests and 82.42 requests per second for 150 requests.